Analysis of Marketing Strategies for Dendrobium Orchids in Semarang City - Edi Gunawan; Titik Ekowati; Florentina Kusmiyati (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
This study analyzes the marketing system of Dendrobium orchids in Semarang City across four product stages (flask, seedling, juvenile, and flowering). The objectives are to measure marketing efficiency and formulate appropriate marketing strategies. The research employed a census method with both quantitative and qualitative approaches, using data obtained through interviews, questionnaires, and observations. Quantitative analyses included marketing margin, farmer’s share, cost–margin ratio (CMR), the Kruskal–Wallis test, and Post Hoc analysis. Qualitative analyses involved SWOT analysis, as well as the IFE, EFE, and IE matrices. The results indicate that the shortest marketing channel is the most efficient, with the highest efficiency found at the flask stage (margin IDR 53,000; farmer’s share 100%; CMR 7,33%), followed by the seedling stage (IDR 5,446; 78.10%; 27.96%), the juvenile stage (IDR 11,538; 72,93%; 19.74%), and the flowering stage (IDR 38,462; 68.41%; 20.13%). The Kruskal–Wallis test revealed significant differences across all three efficiency indicators (p < 0.001), and the Post Hoc analysis confirmed significant differences primarily between the flask and juvenile stages as well as the juvenile and flowering stages. The IFE (2.87) and EFE (2.71) scores positioned the business in the “Hold and Maintain” strategy quadrant, emphasizing market penetration and product development. Recommended strategies include shortening distribution channels, increasing value added at the farmer level, utilizing digital marketing, product innovation, and enhancing price transparency. These findings serve as a reference for farmers, associations, and local government in strengthening competitiveness and ensuring the sustainability of Dendrobium orchid agribusiness in Semarang City.